EP1275 Concordance of peritoneal cancer index using a two-step surgical protocol to select patients for cytoreductive surgery in ovarian cancer. (1st November 2019) - Del, M; Angeles, M; Migliorelli, F; Martínez-Gómez, C; Voglimacci, M; Provendier, A; Bétrian, S; Gabiache, E; Balagué, G; Leclerc, S; Mery, E; Gladieff, L; et al.
Abstract : Introduction/Background: The aim of our study was to assess concordance of the staging laparoscopy and cytoreductive surgery peritoneal cancer index (PCI) when applying a two-step surgical protocol. We also aimed to evaluate the accuracy of diagnostic laparoscopy to triage patients for complete cytoreduction, and to define optimal time between staging laparoscopy and cytoreductive surgery. Methodology: We designed a retrospective review of prospectively collected data from patients with advanced ovarian cancer who underwent a diagnostic laparoscopy followed by a cytoreductive surgery a few weeks later (two-step surgical protocol), from January 2010 to April 2019. Only patients selected for complete cytoreduction, and with available PCI score evaluation during laparoscopy and laparotomy were included. Results: During the study period 543 patients underwent a laparoscopic staging for ovarian carcinomatosis. Among them, 43 patients fulfilled the inclusion criteria. The ICC between laparoscopic and laparotomic PCI was 0.54. After applying the linear regression equation: laparoscopic PCI + 0.2x[Days between surgeries] + 2, ICC increased to 0.79. Completeness cytoreduction score and laparoscopic PCI were significantly associated (OR 1.27). The AUC of laparoscopic PCI to predict a complete cytoreduction was 0.90. Conclusion: The concordance between laparoscopic PCI assessment and PCI score at the end of cytoreductive surgery is fair within a two-step surgical management. Laparoscopic assessment underestimates final PCI score by two points, and this difference increases with the delay between both surgeries. Diagnostic laparoscopy can adequately select patients for cytoreductive surgery, and the optimal time to perform it is no more than ten days after laparoscopy. Disclosure: Nothing to disclose